Functional and structural impacts of oncogenic missense variants on human polo-like kinase 1 protein - Munieswaran, Gayatri; Manickam, Venkatraman (Frontiers in Bioinformatics, 2025)
IntroductionThe polo-like kinase 1 (PLK1), a master key mitotic regulator, is frequently expressed in various types of cancers and associated with poor prognosis. The missense mutations in PLK1 may compromise its structural integrity and functional interactions, contributing to tumorigenesis.MethodsThis study utilized a comprehensive computational pipeline to identify deleterious missense variants across multiple cancers. 207 non-synonymous single nucleotide polymorphisms (nsSNPs) were retrieved from cBioPortal, and 11 high-risk variants were prioritized using functional and structural prediction tools, such as SIFT, PolyPhen-2, I-mutant 2.0, and so on. Prognostic prevalence was evaluated via Kaplan-Meier survival analysis, and functional networks were explored using STRING. The structural dynamics of modeled mutations were analyzed through molecular dynamic simulations over 100 ns.ResultsThe kinase domain mutations such as L244F, R293C, and R293H and polo-box domain mutations such as A520T were found to cause deviations in structural stability, flexibility, solvent exposure, and compactness compared to wild-type. Further, PLK1 overexpression correlated with poor overall survival of patient outcomes in many types of cancers, including breast, liver, lung, kidney, and pancreatic cancers. Protein-protein interaction revealed PLK1’s involvement in oncogenic pathways.DiscussionThe study highlights the structural and functional implications of oncogenic PLK1 mutations, emphasizing their role in cancer progression. Integrating predictive and dynamic exploration approaches facilitates prioritization of variants with potential clinical relevance.ConclusionThe nsSNPs in PLK1 may perturb conformational stability and functions of the protein. Further experimental validation and discovery of novel inhibitors might develop mutation-specific interventions in precision oncology.